Testing sustainability of German fiscal policy : evidence for the period 1960 - 2003 - Alfred Greiner; Uwe Koeller; Willi Semmler (Center for Economic Studies and ifo Institute (CESifo), 2005)
In this paper we test whether German public debt has been sustainable by resorting to a test proposed by Bohn (1998). We apply non-parametric and semi-parametric regressions with time depending coefficients. This test shows that the mean of the coefficient relevant for sustainability has been significantly positive over the time period considered. However, there is a negative trend in that coefficient which seems to have ceased to decline only in the middle to late 1990s. Further, we find evidence that the response of the primary deficit is a Ushaped function of the debt ratio which first declines and then rises after a certain threshold of the debt ratio is exceeded.
Keywords: H63; E62; 330; public debt; intertemporal budget constraint; varying coefficient model; nonparametric estimation; Öffentliche Schulden; Haushaltsdefizit; Finanzpolitik; Verschuldungsrestriktion; Intertemporales Gleichgewicht; Schätzung; Deutschland